Probiotic yeast Kluyveromyces marxianus CIDCA 8154 shows anti-inflammatory and anti-oxidative stress properties in in vivo models - Romanin, David Emmanuel (2015)
Inflammatory bowel diseases (IBDs) are complex affections with increasing incidence worldwide. Multiple factors are involved in the development and maintenance of the symptoms including enhanced oxidative stress in intestinal mucosa. The conventional therapeutic approaches for IBDs are based on the use anti-inflammatory drugs with important collateral effects and partial efficacy. In the present work we tested the anti-inflammatory capacity of Kluyveromyces marxianus CIDCA 8154 in different models. In vitro, we showed that the pretreatment of epithelial cells with the yeast reduce the levels of intracellular reactive oxygen species. Furthermore, in a murine model of trinitro benzene sulfonic acid-induced colitis, yeast-treated animals showed a reduced histopathological score (P<0.05) and lower levels of circulating interleukin 6 (P<0.05). The capacity to modulate oxidative stress in vivo was assessed using a Caenorhabditis elegans model. The yeast was able to protect the nematodes from oxidative stress by modulating the SKN-1 transcription factor trough the DAF-2 pathway. These results indicate that K. marxianus CIDCA 8154 could control the intestinal inflammation and cellular oxidative stress. Deciphering the mechanisms of action of different probiotics might be useful for the rational formulation of polymicrobial products containing microorganisms targeting different anti-inflammatory pathways.